AN APPROACH TO TEACH THE DESCRIPTIVE GEOMETRY COURSE WITH DIGITAL TOOLS IN ARCHITECTURAL EDUCATION - Akbulut, M. Tolga; Daggulu, I. Basak (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2017)
In architectural education, design geometry course is usually given to first year students in order to improve the students' ability of 3-dimensional perception, thinking and solution. In some countries in the world, it is known that this course is also included in the secondary education level more than 100 years. In the 1880s, there were already 14 Realschules, where descriptive geometry was taught in Czech [1]. The school-leaving exam in descriptive geometry was obligatory at Realschules (from German) since the 1870s [2]. In Turkey, in some architectural students are encountering with the course of Descriptive Geometry in architectural education for the first time. For this reason, Descriptive Geometry course, which is a synthetic geometry derivation, is often regarded as one of the most difficult courses by students of architecture. Both the explanation of the course to the students and the understanding of it by the students have technical difficulties. The use of digital tools with the ability to represent 3D, students have tried to overcome the difficulties associated with the narrative of this course and the use of it in the informed architectural design process. In the paper, how to deal with the descriptive geometry course and its contents will be given. The classical explanation methods of the course and the perception and technical problems encountered by the students will be revealed and the course will be evaluated with 3D digital tools and evaluations will be made on the results obtained.
Keywords: Education; Architecture; Design; Descriptive Geometry; 3D; Education & Educational Research